Obstacles in the Implementation of Digital Land Certificates at the Ministry of Agrarian Affairs and Spatial Planning / National Land Agency of The Republic of Indonesia - Asari, Dedy Wahyu; Huda , Miftakhul (Journal of Law, Politic and Humanities, 2025)
The digital transformation of land administration in Indonesia aims to enhance efficiency, transparency, and security in land ownership documentation through the implementation of digital land certificates. However, this system faces several challenges that must be addressed for optimal implementation. The three main obstacles in implementing digital land certificates at the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) are regulatory inadequacies, technological infrastructure limitations, and public resistance. Existing regulations do not fully support digitalization, leading to legal uncertainty and complex coordination between central and local governments. Additionally, unequal technological infrastructure, especially in remote areas, poses challenges in ensuring system accessibility. Public resistance is another significant hurdle, as many still trust physical land certificates over digital documents.